Portfolio selection with CVaR constraint. - Chua, Serene Ee Ling. (2008)
The purpose of this thesis is to develop a portfolio selection approach that is theoretically similar to Markowitz Mean Variance model, that is, to maximize return for a given risk; flexible enough to incorporate a wide variety of assets and risk types; and if possible able to andle portfolios with a large number of assets efficiently.